Chemical Research and Evaluation of the Antioxidant Activity of the Flowers of Annona coriacea Mart. (Annonaceae) - J. Camilo, Cicera; P. Caldas, Rafael; S. Damasceno, Sarah; M.U. Lopes, Cristiane; C.X. Almeida, Sheyla; G.M. da Costa, Jose; F.G. Rodrigues, Fabiola (Current Bioactive Compounds, 2017)
Background: The Annona coriacea Mart. species, popularly known as
Keywords: flavonoids